Tinjauan Hukum Terhadap Penerapan Konsep Zero Waste Dalam Mengatasi Pencemaran Lingkungan Akibat Sampah Dikabupaten Pinrang - Patmawati W, Herlina; Asram A.T Jadda; Hamzah, Hartono; Hidayat, Asrul (Cattleya Darmaya Fortuna, 2025)
This research aims to determine the Zero Waste concept in overcoming environmental pollution due to waste in Pinrang Regency and the effectiveness of existing regulations in supporting the implementation of the Zero Waste concept in overcoming environmental pollution due to waste in Pinrang Regency. This research was carried out in Pinrang Regency, interviews with relevant officials at the Pinrang Regency Environmental Service Office, namely agency leaders, staff in the environmental sector, community leaders, and from the results of analysis and study and interpretation of legal materials which resulted in a discussion and then conclusions were drawn in the form of arguments. Data analysis was carried out using Qualitative Descriptive. The findings obtained from the research include: (1) The Zero Waste concept in overcoming environmental pollution due to waste in Pinrang Regency is based on the 3R principle: Reduce, Reuse and Recycle. This concept has great potential to reduce the impact of environmental pollution, save natural resources, and encourage more responsible consumption paterns in line with existing laws, such as Law Number 18 of 2008 concerning Waste Management, Law Number 32 of 2009 concerning Environmental Protection and Management, and Pinrang Regency Regional Regulation Number 7 of 2013 concerning Waste Management. (2) the effectiveness of existing regulations in supporting the implementation of the Zero Waste concept in overcoming environmental pollution due to waste in Pinrang Regency will be more effective if existing regulations are supported by awareness and active participation from all levels of society, as well as government involvement in providing adequate infrastructure.